Management of Dismenorrhea in Adolescent - Jum Natosba (Arkus, 2017)
The pathophysiological process due to increased myometrium activity caused by excessive production of prostaglandins that cause ischemia. Risk factors are very important in enforcing the diagnosis of dismenorrhea and also in distinguishing between primary and secondary dismenorrhea. Mainstay treatment is generally supportive by relieving symptoms in primary dismenorrhea and surgical treatment may be recommended for secondary dismenorrhea. Therefore, patients with primary dismenorrhea may only require simple non pharmacological and analgesic therapies, whereas patients with secondary menorrhea require treatment for major problems.